2009
DOI: 10.1007/s12022-009-9057-3
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Giant Prolactinoma with Loss of Therapeutic Response to Cabergoline: Expression of Angiogenic Markers

Abstract: The present study reports the case of a 70-year-old Caucasian man who was referred to the Military Hospital of Buenos Aires for evaluation of a giant sellar-extrasellar mass with extension in the right temporal lobe and compression of the third ventricle. Patient was initially responsive to cabergoline with reduction of prolactin levels and shrinkage of tumor burden for at least 36 months. Thereafter, prolactin levels and tumor size increased even though cabergoline dosage was increased. Transcraneal surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Only six such patients have been reported in the literature (excluding malignant transformation) (3,4,5,6,7). The possible explanations for acquired non-responsiveness include non-compliance, onset of gonadal steroid replacement that causes dopamine resistance in the lactotrophs, and, rarely, transformation to carcinoma (37,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only six such patients have been reported in the literature (excluding malignant transformation) (3,4,5,6,7). The possible explanations for acquired non-responsiveness include non-compliance, onset of gonadal steroid replacement that causes dopamine resistance in the lactotrophs, and, rarely, transformation to carcinoma (37,41).…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few reported cases of prolactinoma exhibiting secondary resistance, i.e. cases that show an initial response to dopamine agonists, but then become refractory with prolonged treatment (3,4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Orbital invasion is another rare extrasellar extension of pituitary tumours and will cause exophthalmos and optic nerve compression at the orbital apex (31,46,56). Finally, in the opposite direction, posterior and inferior extension may cause ataxia by cerebellar compression (57,58) or cranio-cervical junction instability (12,13,59). …”
Section: Presenting Featuresmentioning
confidence: 99%
“…Despite invasive features such as bone erosion and extension into surrounding CN structures, mitotic rates and immunohistochemistry for p53 and MIB-1 (Ki67) are often minimally increased (119). On the other hand, one single case study has demonstrated strong immunoreactivity for VEGF and FGF2 (two potent angiogenic factors) and for CD31 (an endothelial marker) in a giant invasive macroprolactinoma, thus suggesting high tumoural vascularization (57). Identification of new molecular markers highly expressed or down-regulated in these giant tumours should help to better understand their origin and progression (27,120) and to find new therapeutic modalities, such as drugs interfering with angiogenesis or cell proliferation.…”
Section: Perspectives In the Management Of Giant Prolactinomasmentioning
confidence: 99%
“…There are only two reports reporting VEGF expression pituitary adenomas using Western blot, one in which a small selection of human pituitary adenomas were evaluated [15] and a second one performed in 24 adenomas, most of which were nonfunctioning [16]. As VEGF immunostaining is highly heterogeneous between adenoma samples [17] and MVD evaluation using immunohistochemistry has some limitations, we wished to study the expression of VEGF and CD31 measured by Western blot in a series of pituitary adenomas in order to add to the comprehension of angiogenic markers in these tumors.…”
Section: Introductionmentioning
confidence: 99%